Representation of The Puragabaya Legend Through Videography of Poetry Musicalization - Adita Widara Putra; Syihabudin Syihabudin; Sumiya Sumiya (Universitas Sebelas Maret, 2022)
The legend of Puragabaya is part of the Galunggung Tasikmalaya folklore which has the potential of Sundanese cultural wealth and needs to be revitalized to maintain its existence. The legend of Puragabaya tells of a special warrior figure Prabu Siliwangi who was educated and forged physically and mentally at the Galunggung Invisibility Pesantren. The figure of Puragabaya contains elements of wisdom, persistence, and tenacity, representing the cultural and social values of the Galunggung community. The revitalization of legends in this study was represented through the videography of poetry musicals. The process of revitalizing the Puragabaya legend is based on the concept of art-based research which aims to present the form of the Puragabaya. The implementation of art-based research to revitalize legends involves the process of creating literary works of art and literary performances consisting of poetry musicalization, poetry reading, and poetry dramatization. In addition, painting and dance work as a form of legend representation are collaborated into videography to add aesthetic power. The results of the study show that the process of revitalizing legends as part of oral literature shows more concrete results by using art-based research that utilizes technological developments.